Trends in rates of incidence, fatality and antimicrobial resistance among isolates of Pseudomonas spp. causing bloodstream infections in England between 2009 and 2018: results from a national voluntary surveillance scheme. (February 2022) - Gerver, S.M.; Nsonwu, O.; Thelwall, S.; Brown, C.S.; Hope, R.
Summary: Background: This article provides baseline epidemiological data on Pseudomonas spp. bloodstream infection (BSI) in England for comparison against future findings from the mandatory surveillance of this infection, beginning April 2017. Aim: To report trends in incidence, 30-day all-cause mortality and antimicrobial resistance of Pseudomonas spp. BSI in England between 2009 and 2018. Methods: Patients and antibiotic susceptibility data were obtained from UK Health Security Agency's voluntary surveillance database. Mortality information was linked from a central data repository. Findings: There were 39, 322 Pseudomonas spp. BSIs between 2009 and 2018. Regression analysis found that the incidence rate was greater by 18.5% ( P <0.01) in the summer (June–August) and by 16.2% ( P <0.01) in the autumn (September–November), compared with spring (March–May). The 30-day all-cause case fatality rate (CFR) declined from 32.0% in 2009 to 23.8% in 2018 ( P <0.001). In 2018, resistance to the key antibiotic agents were: ciprofloxacin (7.5%), ceftazidime (6.8%), piperacillin/tazobactam (6.6%), carbapenems (5.5%) and gentamicin (4.1%). The mortality rate per 100, 000 population was greater by 25.7% ( P <0.01) in autumn and 23.6% ( P <0.01) in winter (December–February). Conclusion: Despite an overall increase in the number of cases in recent years, the percentage of patients dying (from all causes) after a Pseudomonas spp. BSI has been declining. However, compared with other prominent healthcare-associated BSIs, the CFRs are high, and it underscores the need for continued surveillance to support targeted infection control and prevention strategies, provide further understanding of patients' risks groups, and perhaps inform antimicrobial practices.